Reaction Time-Based Fatigue Analysis in Construction Workers - Nicolaus Tommy Raharjo; Shinta Putri Bratakusumah; Ayu Agiel Mujakar (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Occupational fatigue in construction projects remains a critical safety issue, yet its assessment is commonly based on subjective questionnaires and interviews that may not accurately reflect real-time physiological performance. This study aimed to analyze the relationship between biological factors and work-related factors and the level of work fatigue among construction workers using Digital Reaction Timer measurement as an objective indicator. A cross-sectional study was conducted involving active construction workers, where fatigue was quantified using a digital reaction timer as an objective human performance indicator. Biological factors such as age, gender, sleep duration, and nutritional status, as well as work-related factors including working hours, shift patterns, workload, and work experience, were statistically analyzed against reaction time results. The findings show that reaction time measurement can differentiate fatigue levels and identify significant determinants affecting performance degradation. Several biological and occupational variables were associated with increased reaction time, indicating higher fatigue levels. The results demonstrate that an engineering-based digital measurement approach provides a more objective and quantifiable fatigue assessment compared to traditional self-reported methods, supporting data-driven safety management in high-risk construction environments.